Vagal nerve TRPV3 regulates sedative-mediated appeasement - Peiyu Wang; Jinpiao Zhu; Xuteng Lu; Chang Chen; Bomin Gao; Wanjiang Tao; Keyu Xia; Yang Song; Qiong Shi; Hongcun Gai; Panhao Xiao; Feng Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Aromatic essential oils (EOs) exhibit anxiolytic properties, yet their neural and molecular mechanisms remain to be understood. Here, we found that citronellal, an EO derived from lemongrass, alleviates stress-related anxiety by modulating vagal tone. We identified transient receptor potential vanilloid 3 (TRPV3) channel in nodose ganglion (NG) as the molecular target of citronellal. TRPV3 was also observed to mediate the antistress effects of the inhaled anesthetic sevoflurane. Both sedatives attenuated acute restraint stress-induced hyperactivity of heart and breath rates via glutamatergic neurotransmission along NG-to-caudal nucleus tractus solitarius (cNTS) pathway. This effect was abolished by surgical vagotomy, Trpv3 −/− , or NG-specific Trpv3 knockdown. Cryo-EM structural analysis revealed that sevoflurane occupies a pore-proximal fenestration site, while citronellal binds to the vanilloid site. Re-expression of wild-type TRPV3, but not loss-of-function TRPV3 mutants TRPV3(A560L) or TRPV3(V662A), in Trpv3 −/− NG neurons restored the mouse’s response to both sedatives, thereby modulating heart and respiratory rates. Together, these findings establish peripheral TRPV3 as a multisensory ligand-gated node for vagal modulation of stress responses, and help instruct pathway-specific anxiolytics.